ANALISIS PUTUSAN VERSTEK DALAM PERKARA PERCERAIAN STUDI KASUS DI PENGADILAN AGAMA KABUPATEN MALANG - Fiki Fathur Rochman; Ach. Faisol; Dzulfikar Rodafi (Prodi Ahwal syakhshiyyah Fakultas Agama Islam UNISMA, 2019)
Divorce has become a problem in family life when a legitimate bond has run aground amidst travel in the family. In this case, seeing many divorce cases in the Malang District Religious Court, the researchers also looked for the problem side, not the problem of divorce, using the verdict. Decisions that have been dropped by the Judge to the second party who are litigating by the Defendant are also the Respondent. The researcher was more interested in the verdict seen from the absence of the parties in this case the Verstek ruling. Where this Verstek ruling was seen from the absence of the Defendant in the trial. So the type in this study uses Kaulitative research using interview methods and documentation. In his case the Verstek verdict in the Malang District Religious Court obtained high results from the hard work of the research proving April 2019 data from 687 The verdict that the Verstek decision reached 442 Verstek Decisions. This shows a very high number can be further about the factors associated with the Defendant's absence.Kata Kunci : Perceraian, Putusan, Putusan Verstek